Takhrij and Syarah Hadith of Agrotechnology: Ingredients and Benefits of Dates - Fildzah Rahimah; Wahyudin Darmalaksana; Budy Frasetya TQ (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The result and discussion of this research is that dates are a special fruit according to the hadith of the Prophet with potassium which is beneficial for health. The conclusion of this research is that the takhrij and syarah hadith of the Prophet SAW regarding dates with agrotechnology analysis have a wider development opportunity.